Human papillomavirus prevalence and vaccine effectiveness in young women in Germany, 2017/2018: results from a nationwide study - Loenenbach, Anna; Schönfeld, Viktoria; Takla, Anja; Wiese-Posselt, Miriam; Marquis, Adine; Thies, Sarah; Sand, Matthias; Kaufmann, Andreas M.; Wichmann, Ole; Harder, Thomas (Frontiers in Public Health, 2023)
Background Infections with human papillomaviruses (HPV) are sexually transmitted and can cause cancer. In Germany, vaccination against HPV is recommended for girls and boys aged 9–17 years. We aimed to investigate HPV DNA prevalence, genotype distribution and vaccine effectiveness (VE) in women aged 20–25 years 10 years after the introduction of HPV vaccination in Germany (2018–2019), and compared these data to an equally designed study from 2010–2012. Methods Seventy six geographical clusters were randomly selected, followed by random selection of 61 women aged 20–25 years per cluster. Participants performed cervicovaginal self-sampling and answered questions on demographics, sexual behaviour and HPV vaccination. Samples were tested for 18 high risk and nine low risk HPV genotypes. We performed chi-square tests, Fisher’s exact test, unpaired Student’s t-test and proportion t-test, and calculated crude and adjusted prevalence ratios (PR) and 95% CIs. Results Of 7,858 contacted women a total of 1,226 agreed to participate. Of these, 94 women were positive for HPV types 16 and/or 18. HPV16 prevalence was 7.0% (95% CI 5.6–8.6) and HPV18 prevalence was 0.8% (95% CI 0.4–1.5). HPV6 and HPV11 were rare with only five (0.4%; 0.1–0.9) and one (0%; 95% CI 0.0–0.5) positive tests. Seven hundred fifty-seven women (62%) had received at least one HPV vaccine dose and 348 (28%) were vaccinated as currently recommended. Confounder-adjusted VE was 46.4% (95% CI 4.2–70.1) against HPV16/18 infection and 49.1% (95% CI 8.2–71.8) against infection with at least one HPV genotype covered by the quadrivalent HPV vaccine. Compared with the 2010–2012 study results, HPV16/18 prevalence dropped from 22.5% (95% CI 19.0–26.3) to 10.3% (95% CI 7.5–13.9; p < 0.0001) in unvaccinated participants. Conclusion Vaccine-covered HPV genotypes were rare among 20–25 years old women in Germany and decreased compared to the time point shortly after the start of the HPV vaccination program. HPV prevalence of almost all vaccine-covered genotypes was strongly reduced in vaccinated participants. A decrease of HPV16 and HPV18 was even observed in unvaccinated participants, compared to 2010–2012 data, suggesting indirect protection of unvaccinated women. Low VE against HPV16/18 and HPV6/11/16/18 in our study might be attributable to study design in combination with the endpoint selection of (mainly transient) HPV DNA positivity.